Y box binding protein 1 inhibition as a targeted therapy for ovarian cancer. Issue 8 (19th August 2021) - Tailor, Dhanir; Resendez, Angel; Garcia-Marques, Fernando Jose; Pandrala, Mallesh; Going, Catherine C.; Bermudez, Abel; Kumar, Vineet; Rafat, Marjan; Nambiar, Dhanya K.; Honkala, Alexander; Le, Quynh-Thu; Sledge, George W.; et al.
Summary: Y box binding protein 1 (YB-1) is a multifunctional protein associated with tumor progression and the emergence of treatment resistance (TR). Here, we report an azopodophyllotoxin small molecule, SU056, that potently inhibits tumor growth and progression via YB-1 inhibition. This YB-1 inhibitor inhibits cell proliferation, resistance to apoptosis in ovarian cancer (OC) cells, and arrests in the G1 phase. Inhibitor treatment leads to enrichment of proteins associated with apoptosis and RNA degradation pathways while downregulating spliceosome pathway. In vivo, SU056 independently restrains OC progression and exerts a synergistic effect with paclitaxel to further reduce disease progression with no observable liver toxicity. Moreover, in vitro mechanistic studies showed delayed disease progression via inhibition of drug efflux and multidrug resistance 1, and significantly lower neurotoxicity as compared with etoposide. These data suggest that YB-1 inhibition may be an effective strategy to reduce OC progression, antagonize TR, and decrease patient mortality. Graphical abstract: Highlights: Azopodophyllotoxin small molecule, SU056, inhibits YB-1 YB-1 inhibition decreases OC cell proliferation and resistance to apoptosis YB-1 inhibition sensitizes OC cells for paclitaxel treatment Abstract : Tailor et al. reported azopodophyllotoxin derivative SU056 as a Y box binding protein 1 (YB-1) inhibitor. YB-1 inhibitor co-treatment sensitizes ovarian cancer cells for paclitaxel treatment.